2014
DOI: 10.1177/0954008314564197
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of high-strength microporous phenolic open-cell foams with physical foaming method

Abstract: A series of high-strength and highly microporous phenolic open-cell foams modified by different epoxy resins were fabricated using physical foaming method. The new compound emulsifiers consisting of anionic and nonionic surfactants were physical blended at high speed with modified resols, foaming agent, and mixed acid curing agent. The modified synthesis of epoxy-modified phenol-formaldehyde (PF) resin was conducted via the etherification mechanism. In order to verify the occurrence of etherification mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Therefore, the mechanical properties decreased. 16 In addition, it had been seen that by increasing the amount of surfactant the structure of the foams became irregular [ Figure 7(d)]. Figure 13 shows stress-strain curve and the variation of the specific mechanical properties by increasing the viscosity.…”
Section: Mechanical Properties Of Foamsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the mechanical properties decreased. 16 In addition, it had been seen that by increasing the amount of surfactant the structure of the foams became irregular [ Figure 7(d)]. Figure 13 shows stress-strain curve and the variation of the specific mechanical properties by increasing the viscosity.…”
Section: Mechanical Properties Of Foamsmentioning
confidence: 99%
“…5 Other studies had been performed on the effect of viscosity and surfactant on the cell morphology of phenolic foams. [13][14][15][16] Another parameter that affects cell structure, density, and mechanical properties of foam is ambient pressure. Shewen Lie et al demonstrated that by increasing the ambient pressure, the bubbles shrinked and the cell structure became more integrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that all foams exhibited a multistage deformation response when subjected to compressive loading, i.e. an initial linear elasticity region (I) (0%–0.5%) controlled by the overall elastic bending of cell walls, a continuously increasing region (II) (0.5%–10%) depending on the collapse of weak cells and a yield plateau region (III) (>10%) accompanied by the complete collapse and contact between opposing cell walls …”
Section: Resultsmentioning
confidence: 99%
“…Improvement in these properties can be achieved by chemical modification, the addition of inert fillers, and fiber reinforcement. [ 12 ] Among the different methods, the chemical modification method has gained more attention for its notable toughening effect. Highly flammable foams such as polyurethane and polystyrene can be replaced with PF for building thermal insulation materials.…”
Section: Introductionmentioning
confidence: 99%